The Party Goes On: U.S. Young Adults' Partisanship and Political Engagement Across Age and Historical Time. Issue 6 (November 2019) - Wray-Lake, Laura; Arruda, Erin H.; Hopkins, David A.
This article examines effects of political party affiliation on U.S. young adults' political participation across age and historical time. Using national U.S. longitudinal Monitoring the Future data from youth aged 18 to 30 years, we estimate effects of partisanship (Democrat, Republican, Other) on change in youth's electoral and political voice participation with age, and test whether effects differ between 1976 and 2003. Political engagement and partisanship declined for young adults over several decades. Partisanship had a consistent positive effect on electoral participation across age and cohort. Democratic youth were higher on nonelectoral participation for some cohorts, and Democrats and Republican youth showed growth in nonelectoral participation at different historical moments. Although younger cohorts of Americans are less politically engaged based on available measures, political parties still remain a powerful force for political participation among those who choose to affiliate. Youth's partisan attachments and political behavior are best understood in historical context.